Propagating cassava (Manihot esculenta) by sexual seed - Iglesias, C.A.; Hershey, Clair H.; Calle, F.; Bolaños, A. (Cambridge University Press, 1994)
Commercial cassava production from true cassava seeds (TCS) appears to be a promising option for reducing or eliminating several of the production constraints associated with vegetative propagation. The most important contribution of TCS would be to reduce virus build-up in vegetative material and to resolve the problems of stake storage, low multiplication rate and the long growth cycle. Preliminary results suggest that the root yield potential of TCS is comparable with that of traditional vegetative propagation. Improvements in the capacity of true seed progenies to germinate and establish in the field can be achieved either genetically or through pre-planting seed treatments such as coating the seed with rock phosphate. Development of a successful TCS technology will require a multidisciplinary approach, involving basic studies in cassava breeding, physiology, agronomy, socio-economics and other fields.